2017
DOI: 10.5152/npa.2017.19257
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of OnabotulinumtoxinA Treatment in Patients with Concomitant Chronic Migraine and Temporomandibular Disorders

Abstract: Introduction: Migraine and temporomandibular disorders (TMD) are both common diseases and TMD are reported as a risk factor in migraine progression. OnabotulinumtoxinA is used in the treatment of chronic migraine (CM), and also has a potential role in TMD treatment. In this study, it is aimed to compare the efficacy of onabotulinumtoxinA treatment in CM patients with and without TMD. Methods: In this retrospective study, 30 CM patients (age range: 18-65 years), satisfying the inclusion and follow-up criteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
2
0
4
Order By: Relevance
“…Outro estudo citou como forma de avaliação da qualidade de vida a utilização de escala visual para o paciente marcar a percepção de impacto da doença em seu dia a dia, a qual foi considerada pelo próprio autor uma forma simples de julgamento visto que não utilizou questionários específicos para avaliação de bem estar (Farrier et al, 2020). O terceiro artigo que explorou melhora de qualidade de vida, utilizou questionários específicos para cefaleia, com indicadores demográficos, aferições de freqüência de sintomas, investigação de necessidade de terapia farmacológica diária e média cumulativa de horas com dor (Kocaman et al, 2018).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Outro estudo citou como forma de avaliação da qualidade de vida a utilização de escala visual para o paciente marcar a percepção de impacto da doença em seu dia a dia, a qual foi considerada pelo próprio autor uma forma simples de julgamento visto que não utilizou questionários específicos para avaliação de bem estar (Farrier et al, 2020). O terceiro artigo que explorou melhora de qualidade de vida, utilizou questionários específicos para cefaleia, com indicadores demográficos, aferições de freqüência de sintomas, investigação de necessidade de terapia farmacológica diária e média cumulativa de horas com dor (Kocaman et al, 2018).…”
Section: Resultsunclassified
“…Um terço dos artigos não apresentou grupo controle e seus autores mensuraram no mesmo grupo os efeitos antes e após a intervenção com toxina botulínica A (Freund et al,2002;Sidebotton et al, 2013;Baker, 2017;Kocaman, et al, 2018;Khan, 2018;Daily et al, 2021;Al-Hussain et al, 2021;Alshalah et al,2021;Oksanen et al, 2022).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…However, the possible effectiveness of the PREEMPT protocol on TMD comorbid symptoms has not been investigated properly. In 2018, Kocaman et al found that the presence of TMD symptoms did not constitute a predictive factor for response to BoNT-A treatment in a population of 30 patients with CM [74,75]. The possible mechanism of action of BoNT-A on comorbid TMD and migraine has been investigated by Lacković et al on an animal model.…”
Section: Effects On Interictal Symptoms and Comorbiditymentioning
confidence: 99%